The effectiveness of intermittent theta burst stimulation for upper limb motor recovery after stroke: a systematic review and meta-analysis of randomized controlled trials - Chen, Songbin; Zhang, Shunxi; Yang, Wenqing; Chen, Yujie; Wang, Bingshui; Chen, Jixiang; Li, Xiaotong; Xie, Lanfang; Huang, Huangjie; Zeng, Yangkang; Tian, Lingling; Ji, Wenxue; et al. (Frontiers in Neuroscience, 2023)
Background: Intermittent theta burst stimulation (iTBS) is a promising noninvasive therapy to restore the excitability of cortex, and subsequently improve the function of upper extremity. Several studies have demonstrated the effectiveness of iTBS in restoring upper limb function and modulating the cortical excitability. We aimed to evaluate the effects of iTBS on upper limb motor recovery after stroke.Objective: The purpose of this article is to evaluate the influence of intermittent theta-bust stimulation on upper limb motor recovery and improve the quality of life.Method: A literature search was conducted using PubMed, EMBASE, MEDLINE, The Cochrane Library, Web of Science, CBM, including only English studies, to identify studies that investigated the effects of iTBS on upper limb recovery, compared with sham iTBS used in control group. Effect size was reported as standardized mean difference (SMD) or weighted mean difference (WMD).Results: Ten studies were included in the meta-analysis. The results of the meta-analysis indicated that when compared to the control group, the iTBS group had a significant difference in the Fugl-Meyer Assessment (FMA) and Action Research Arm Test (ARAT) (WMD:3.20, 95%CI:1.42 to 4.97; WMD:3.72, 95%CI:2.13 to 5.30, respectively). In addition, there was also a significant improvement in modified Ashworth scale (MAS) compared to the sham group (WMD: -0.56; 95% CI: -0.85 to -0.28). More evidence is still needed to confirm the effect of Barthel Index (BI) scores after interventions. However, no significant effect was found for the assessment of Motor Evoked Potential (MEP) amplitude and MEP latency (SMD: 0.35; 95% CI: -0.21 to 0.90; SMD: 0.35, 95% CI: -0.18 to 0.87; SMD: 0.03, 95% CI: -0.49 to 0.55; respectively). Conclusions: Our results showed that iTBS significantly improved motor impairment, functional activities, and reduced muscle tone of upper limb, thereby increasing the ability of Activities of Daily Living (ADL) in stroke patients, while no significant differences in MEPs. In conclusion, iTBS is a promising non-invasive brain stimulation as an adjunct to therapy and enhances the therapeutic effect of conventional physical therapy. In the future, more randomized controlled trials with large sample size, high quality, and follow-up are necessary to explore the neurophysiological effects.